Analisis Wacana Pesan Edukasi Pemilu pada Program “Warung Pengkolan” Episode 03 di TVRI Nasional - Didi Alzi Purnomo; Makroen Sanjaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Ahead of the election which will be held in February 2024, television is competing to broadcast various educational talk show programs, especially regarding elections or politics, one of which is TVRI Nasional. Ideally, people choose with their own thoughts and views. However, in reality there are still many people who choose randomly without logical reasons or just go along with it, even worse, they are indifferent to the election. The purpose of this research is to find out what educational messages are contained and how the educational messages contained in